2023
DOI: 10.1097/shk.0000000000002189
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Supplemental Hemoadsorption Therapy on Severe and Critical Patients With Covid-19: An Evidence-Based Analysis

Junbing He,
Yao Lin,
Weiming Cai
et al.

Abstract: Background The COVID-19 pandemic has posed a disproportionately high threat to the global health system and social stability. COVID-19 damage can lead to hyperinflammation and tissue damage due to a "cytokine storm", which in turn contributes to an increase in the mortality rate. Extracorporeal hemoadsorption therapy (HAT) in patients with severe COVID-19 may improve organ function and stabilize hemodynamic status; however, the effects of supplemental HAT remain controversial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…This indicates that many molecules can function as drug targets in COVID-19 associated cytokine storm if they are part of central inflammatory pathways. Reducing the general levels of circulating cytokines through hemoadsorption, remains more controversial, as some studies report a decrease in mortality, while others have found no improvement or even negative effects on survival [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that many molecules can function as drug targets in COVID-19 associated cytokine storm if they are part of central inflammatory pathways. Reducing the general levels of circulating cytokines through hemoadsorption, remains more controversial, as some studies report a decrease in mortality, while others have found no improvement or even negative effects on survival [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, initial mutants of the virus cause severe COVID-19, and infected patients admitted to the intensive care unit (ICU) usually first present with pneumonitis combined with increased oxygen demand, often leading to acute respiratory distress syndrome (ARDS) and multiple additional symptoms, for example, vasculitis or renal failure, frequently linked to increased inflammation. Addressing the inflammatory processes has become an elementary therapeutic concept but is not highly specific (2)(3)(4)(5). It has been postulated that inflammatory symptoms can be linked to a dysregulated kinin-kallikrein-system (KKS) and renin-angiotensin-aldesterone system (RAAS), leading to a "bradykinin storm" in multiple tissues and systems, resulting finally in observed COVID-ARDS and multiple organ failure (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%